2010
DOI: 10.1149/1.3339449
|View full text |Cite
|
Sign up to set email alerts
|

Bipolar Resistive Switching Memory Using Cu Metallic Filament in Ge[sub 0.4]Se[sub 0.6] Solid Electrolyte

Abstract: service Email alerting click here top right corner of the article or Receive free email alerts when new articles cite this article -sign up in the box at the http://esl.ecsdl.org/subscriptions go to: Electrochemical and Solid-State Letters To subscribe toA bipolar resistive switching memory device with a low power operation ͑200 A ϫ 1.3 V͒ in a W/Ge 0.4 Se 0.6 /Cu/Al structure is investigated. A high quality Ge 0.4 Se 0.6 solid electrolyte is confirmed by X-ray photoelectron spectroscopy. The resistive memory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
36
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(41 citation statements)
references
References 13 publications
5
36
0
Order By: Relevance
“…The nanoscale filament diameter was 10.4 to 0.17 nm as the CC decreased from 500 to 0.1 μA. These calculated filament diameters were generally consistent with those in some reports [26,32,50] but were slightly different than others in the literature [33,51], which may be due to different solid-electrolytes and structures used. The observed small diameter of 1.7 Å at a small CC of 0.1 μA indicates that this device will be scalable beyond the atomic scale in the future.…”
Section: Resultssupporting
confidence: 87%
“…The nanoscale filament diameter was 10.4 to 0.17 nm as the CC decreased from 500 to 0.1 μA. These calculated filament diameters were generally consistent with those in some reports [26,32,50] but were slightly different than others in the literature [33,51], which may be due to different solid-electrolytes and structures used. The observed small diameter of 1.7 Å at a small CC of 0.1 μA indicates that this device will be scalable beyond the atomic scale in the future.…”
Section: Resultssupporting
confidence: 87%
“…As presented in Fig. 3(d), the filament diameters are consistent with some previously reported results 4,7,14,25 but slightly different to others, 16,18,26,27 because of the different solid electrolytes, structures, and current overshoot effects. Owing to the Cu/GeO x /W structure design, enhanced resistive switching performance can also be realized in the future, as discussed below.…”
Section: -supporting
confidence: 91%
“…Good data retention with high resistance ratios of 10 Resistive switching random access memory devices have shown promise for developing low power nanoscale nonvolatile memory technology in the future. [1][2][3][4][5] Many previous studies of this topic have reported solid electrolyte-based resistive switching memory devices that use different materials, such as GeSe x , [6][7][8] CuTe/Al 2 O 3 , 13 and GeSe x /TaO x. 14 Resistive switching occurs because of the formation/dissolution of the silver (Ag) or Cu metallic filament under external bias.…”
mentioning
confidence: 99%
“…Stable resistance ratio of >200 is obtained, which is lower than the mentioned as in I-V characteristics. Generally, the value of HRS is decreased after few cycles, as reported previously [12], however this thermally grown GeSe x film has benefit to have unchanged HRS even after 200 cycles. To obtain stable program/erase (P/E) cycles, good structure with a switching material is necessary to design, which is observed here.…”
Section: Resultssupporting
confidence: 76%